2019
DOI: 10.1039/c9ra06385d
|View full text |Cite
|
Sign up to set email alerts
|

A novel quartz-crystal microbalance humidity sensor based on solution-processible indium oxide quantum dots

Abstract: A high-performance QCM humidity sensor was prepared based on In2O3 QDs with a high specific surface area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Moreover, extreme conditions of humidity have adverse effects on human health and are linked to many diseases . Different types of humidity sensors have been developed based on either solid-state devices, , flexible substrates, inkjet printed textile, or textile fiber composite materials. , Most of these studies demonstrated the sensitivity of the sensor; however, only a few of these discussed the selectivity of the sensor, which is equally important. Moreover, in the case of textile-based humidity sensors, to the best of our knowledge, there is no report describing the selectivity of the textile sensors in the presence of interferences such as volatile organic compounds (VOCs).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, extreme conditions of humidity have adverse effects on human health and are linked to many diseases . Different types of humidity sensors have been developed based on either solid-state devices, , flexible substrates, inkjet printed textile, or textile fiber composite materials. , Most of these studies demonstrated the sensitivity of the sensor; however, only a few of these discussed the selectivity of the sensor, which is equally important. Moreover, in the case of textile-based humidity sensors, to the best of our knowledge, there is no report describing the selectivity of the textile sensors in the presence of interferences such as volatile organic compounds (VOCs).…”
Section: Introductionmentioning
confidence: 99%
“…By exposing the sensor to different RH environments achieved through different saturated salt solutions, the humidity-sensing characteristics were studied. The RH of the saturated aqueous solutions of LiBr, LiCl, MgCl 2 , K 2 CO 3 , Mg(NO 3 ) 2 , KI, NaCl, KCl, and KNO 3 in a closed container are about 6.9%, 11.3%, 33.3%, 43.2%, 59.0%, 71.0%, 75.6%, 85.9%, and 95.4% at room temperature [32].…”
Section: Resultsmentioning
confidence: 99%